Influencing factors of students’ willingness to communicate in english in the EFL classroom: a systematic review - Dong, Yan; Ahmad, Norhakimah Khaiessa; Che Nawi, Nur Raihan (Penerbit UTM Press, 2023)
Willingness to communicate (WTC) has been considered a research hotspot in second language acquisition and foreign language teaching. However, systematic analysis of factors influencing students’ WTC in English is scarce. This systematic review aims to explore and summarize existing research on factors influencing students’ English WTC published from 2013 to 2022. According to the selection criteria, a total of 25 relevant publications are included in the scope of analysis, which has been categorized into internal and external factors. Both of these factors influence students’ English WTC. The results showed that most of the studies were concentrated among Middle East participants and the quantitative approach was dominant in these studies. This review revealed that the factors have become more diversified, such as emotional intelligence, ethnic group affiliation, and digital game-based learning. The factors include not only internal and external factors, but there is also a growing trend examining the comprehensive factors including individual factors, affective factors, and learning environment that affect students’ WTC in English. Finally, this study may benefit English teachers, researchers, and educators who aspire to improve students’ English WTC by providing a detailed review of the factors influencing students’ English WTC. It concludes with recommendations for future research to study students’ WTC in English